EFFECTS OF POLLEN TYPHAE TOTAL FLAVONE ON β-ARRESTIN-2/SRC/ AKT SIGNALING IN ADIPOSE TISSUES OF TYPE 2 DIABETIC RATS - Feng, Xiao-Tao; Zhai, Lin-Na; Wang, Chun-Ling; Zhao, Wei; Chen, Qun; Huang, Xiao-Qi (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Pollen Typhae total flavone (PTF), the extract from Pollen Typhae, a Chinese herbal medicine, has been reported to improve insulin resistance in type 2 diabetic rats, but the potential mechanisms keep unclear. Materials and Methods: Type 2 diabetic model rats were induced by high-fat diet and low-dose streptozotocin, and then were administered PTF by intragastrical gavage. After treatment for 4 weeks, insulin receptor-β level in adipose tissues was determined by ELISA, and the protein expression was analyzed by western blotting. Results: Administration of PTF increased insulin receptor-β level and enhanced β-arrestin-2 protein expression in adipose tissues of type 2 diabetic rats. Although having no effect on the protein expression of Src or Akt, PTF promoted phosphorylation of Src at Tyr416 and Akt at Ser473. Conclusion: The results indicate that PTF has beneficial effects on the β-arrestin-2/Src/Akt signaling in adipose tissues of type 2 diabetic rats, implying the underlying mechanisms of PTF in ameliorating insulin resistance.